Pendidikan Karakter Yang Terintegrasi Dengan Budaya Organisasi - Ramdani; Darman Eka Saputra; Reza Faizal; Weni Novitasai; Nur Azizah (Jurnal Adijaya Multidisplin, 2024)
The implementation of organizational fundamentals, such as a clear vision and mission, inspiring leadership, strong organizational culture, and a transparent evaluation system, can significantly increase the effectiveness of character education. In addition, the integration of character education into the curriculum and extracurricular activities is also a determining factor in the formation of student character. This study concludes that character education based on organizational fundamentals not only improves the moral quality of individuals, but also creates a conducive educational environment for the holistic development of students. Community service activities that focus on the implementation of character education based on organizational fundamentals at SMK Yapia Parung, Bogor Regency. This activity aims to strengthen character values among students through a structured approach based on organizational principles. The method used in this activity is a seminar. The implementation of the activity begins with a needs analysis and determination of the vision and mission of character education that is in accordance with the culture and values of the School. Furthermore, intensive training is carried out to integrate character values into the learning process and extracurricular activities. The character programs developed include various activities such as group discussions, community service projects, and competitions that encourage positive behavior. The results of the activity showed a significant increase in awareness and application of character values by students, as well as improvements in the school climate that is more conducive to learning. Continuous evaluation through surveys and observations shows that the organizational-based character education approach has a positive impact on the development of students' morals and ethics.